SLANG WORDS USED IN RIDE ALONG 2 MOVIE - I Gede Agus Reval Aryana Putra Jaya; I Wayan Mulyawan; Ketut Santi Indriani (CV. Ulil Albab Corp, 2022)
Abstract: This study is aimed to identify the types of slang words and analyse the meaning of slang words. The data were taken from a movie entitled Ride Along 2. The data were collected through observation method which the technique is documentation, in order to find the movie script, select and classify the types of slang words. The data then were identified to find the types of slang words using the concept of slang proposed by Chapmann (1988) and the concept of meaning proposed by Leech (1974) was used to analyse the meaning of slang words. The data were discovered that there were 20 data of secondary slang dominantly used in the movie and 12 data of primary slang were not used as much as the secondary slang. After discovering the types of slang words, the meaning of slang words then were analysed and found that 17 data of connotative meaning used more dominant. Several meanings of slang word are found and mostly expressed by someone who tries to express the feeling or emotion of getting mad or surprised. Slang words mostly contain a certain domain such as violence, crimes, and sexuality.